A Fiscal Price Tag for International Reserves - Hauner, David (IMF Working Papers; Working Paper ;, 2005)
This paper examines the (quasi-)fiscal impact of the (opportunity) cost of international reserves. It proposes a conceptual framework, with particular emphasis on two hitherto somewhat neglected aspects: a more appropriate measure of gross opportunity cost, and potential savings from lower external debt spreads that countries "buy" by holding reserves. The framework is then applied to 100 countries over 1990-2004. The results suggest that a turning point has been reached in recent years: while most countries made money on their reserves during 1990-2001, most have been losing money during 2002-04.